2013
DOI: 10.4315/0362-028x.jfp-13-011
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli Contamination of Lettuce Grown in Soils Amended with Animal Slurry

Abstract: A pilot study was conducted to assess the transfer of Escherichia coli from animal slurry fertilizer to lettuce, with E. coli serving as an indicator of fecal contamination and as an indicator for potential bacterial enteric pathogens. Animal slurry was applied as fertilizer to three Danish agricultural fields prior to the planting of lettuce seedlings. At harvest, leaves (25 g) of 10 lettuce heads were pooled into one sample unit (n = 147). Soil samples (100 g) were collected from one field before slurry appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 46 publications
1
11
1
Order By: Relevance
“…One soil drag sample was positive on the same farm for Salmonella spp. These results support that detection of generic E. coli in spinach at high levels could be considered an indicator of a recent exposure to risk factors for Salmonella and potentially other foodborne pathogens (46), as it has been envisioned by the recent initiative of the EFSA to use E. coli as a hygiene criterion in the production of leafy greens (8).…”
Section: Discussionsupporting
confidence: 74%
“…One soil drag sample was positive on the same farm for Salmonella spp. These results support that detection of generic E. coli in spinach at high levels could be considered an indicator of a recent exposure to risk factors for Salmonella and potentially other foodborne pathogens (46), as it has been envisioned by the recent initiative of the EFSA to use E. coli as a hygiene criterion in the production of leafy greens (8).…”
Section: Discussionsupporting
confidence: 74%
“…The contamination of plant food such as lettuce with E. coli has been shown to happen by the transfer from slurry fertilizer, with E. coli serving as an indicator of fecal contamination and potential bacterial enteric pathogens. 26 Coliform contaminations in fertilized soil generally persist for more than 100 days after the application of manure with a decrease of ∼1 log 10 per month from the initial levels of about 4 log 10 CFU g −1 . Photodynamic Decontamination based on a cationic derivate of curcumin induces an antibacterial effect (3 log 10 criterion) at concentrations of the photoactive compound of 10 µM or higher on samples with a "flat" geometry, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The survival of food-borne pathogens is a potential threat to humans, and is far more important than any other quality aspect. Jensen et al (2013) reported the transfer of E. coli from animal slurry fertilizer to lettuce. This occurred in a pilot study in which animal slurry was applied as fertilizer in three Danish agricultural fields, prior to the planting of lettuce seedlings, with E. coli serving as an indicator of fecal contamination and of potential bacterial enteric pathogens.…”
Section: Growing Conditions and Raw Materials Productionmentioning
confidence: 99%